Moving beyond living arrangements: the role of family and friendship ties in promoting mental health for urban and rural older adults in China. (1st September 2020) - Tang, Dan; Lin, Zhiyong; Chen, Feinian
Abstract: Objective: This study examines the interplay among living arrangements, social networks, and depressive symptoms among Chinese older adults. Methods: Data are derived from the 2014 baseline survey of the China Longitudinal Aging Social Survey (CLASS), which provides a sample of older Chinese who had been married and had children ( N = 7, 662). This study examines the association between living arrangements and depressive symptoms (measured as CES-D scale, 0–18) of older adults, and addresses the moderating role of social networks (measured as family ties and friendship ties, 0–15) on this perceived association. Results: Our results show that older adults who live both with a spouse and adult children report superior mental health than those living alone ( β = 1.240, p < 0.001), but no differences are seen from those living only with a spouse or children. Older adults living alone in rural areas are also more disadvantaged in comparison to those living alone in urban places ( β = 0.535, p < 0.05). However, we find that the undesirable consequences associated with depression of older adults living alone can be reduced or even eliminated when older adults have strong friendship ties in rural China ( β = −0.145, p < 0.01). We also find that for rural older adults living only with children, their mental health is highly contingent on their family ties, that is, they are extremely disadvantaged when having weak family ties, but benefit most significantly from strong family ties ( β = −0.137, p < 0.05). Conclusions: Associations between living arrangements and mental health in later life are contingent on older adults' social networks, and these moderating effects vary between rural and urban China.